INTELLIGENT NIGHT VISION SYSTEM FOR AUTOMOBILE BASED ON COMPUTER VISION- A REVIEW (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
No one in this world is willing to face the accidents while travelling, human safety is really important and hence to avoiding the accidents is also essential. It is found in study that most of the accidents occurred all over the world are due to insufficient night vision. The accidents may damage the automobile and human life is in danger as well. Many researchers and R&D organisations have suggested the changes in the design of vehicles from safety point of view. In the era of smart world, it is need of time to, design and implement the smart night vision system for automobiles. Authors have proposed the intelligent night vision system for automobiles based on computer vision in this paper.